Tax Fairness and Tax Morality as Perceived by Private Higher Education Institution Instructors in Tagum City - Mary Cris L. Luzada; Andre M. Alesna; Cris Lyka V. Caresosa; Kristine Ara H. Bogoy (Future Science / FSH-PH Publications, 2026)
This study investigated the relationship between tax fairness and tax morality among private higher education institution instructors in Tagum City, and sought to fill the gaps in the existing literature. The study also identified the indicators of tax fairness that had the greatest influence on the tax morale of the respondents. The adapted and modified questionnaire was tested for validity and reliability before being used to collect data from 220 private HEI instructors across 8 colleges in the city. This study, using a quantitative correlational research design, employed the following statistical tools: mean, Pearson-r, and multiple regression analysis. The results of this study revealed that tax fairness and tax morality are significantly related with an r-value of 0.621 and a p-value of 0.001. The general fairness, vertical fairness, and administrative fairness, 3 of 5 indicators of tax fairness, were also found to influence tax morale significantly. Through the lens of the Theory of Planned Behavior, the results suggest that an individual's perception of taxes plays a crucial role in promoting voluntary compliance with the fiscal framework. As the perception of tax fairness increases, instructors' tax morale also increases. Thus, the government should prioritize transparency and efficiency within tax authorities and across their operations to boost voluntary tax compliance among private HEI instructors. It is also recommended that tax authorities improve the tax system by simplifying the filing process, enhancing transparency in revenue allocation, and refining the apportionment of the tax burden among taxpayers.